Exploring Sharia-Based Economic Potential: The Role of Cooperatives and Insurance in Enhancing Ummah Welfare - Muhidin Muhidin; Akbar Muhamad Ashoni (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2026)
The sharia economy in Indonesia has experienced significant growth and has become an integral part of the national economic system. Sharia cooperatives and sharia insurance play a strategic role in strengthening the people’s economy, particularly through microeconomic empowerment and sharia-compliant risk management. However, rapid institutional growth has not been fully accompanied by conceptual clarity and consistent implementation of fiqh muamalah principles, resulting in ongoing academic and practical debates. This study employs a qualitative descriptive-analytical approach based on library research. Primary data sources include the Qur’an, Hadith, classical fiqh literature, national regulations on cooperatives and Islamic financial institutions, and fatwas issued by the National Sharia Council (DSN-MUI). Secondary data are drawn from relevant academic journals and scholarly works. Data were analyzed using content analysis to examine the conformity of sharia cooperative and sharia insurance practices with fiqh muamalah principles. The findings indicate that sharia cooperatives play a vital role in providing riba-free financing, expanding access to capital for micro and small enterprises, and strengthening the socio-economic foundations of the ummah. Nevertheless, practical implementation reveals a tendency toward adopting conventional financial patterns, particularly in contract structures and profit orientation. This situation potentially undermines the substantive values of ta‘awun and risk sharing, highlighting a tension between the normative ideals of Islamic economics and institutional realities. This study concludes that sharia cooperatives and sharia insurance possess substantial potential to support a just and sustainable Islamic economic system. However, reinforcing conceptual foundations and ensuring consistent application of fiqh muamalah principles are essential to preserve their sharia integrity and socio-economic objectives.